1989
DOI: 10.1002/pssb.2221550234
|View full text |Cite
|
Sign up to set email alerts
|

Incommensurate Magnetic Structures in Triangular Antiferromagnet CsCuCl3

Abstract: The helical magnet CsCuC1, in an applied field higher than the critical field is shown to have sinusoidal phase with linear polarization of spins. The new intermediate phase is due to a conical-point instability caused by weak dipole interactions. Therefore in different temperature ranges two modulated structures are actually realized. Results found theoretically are in good agreement with the experimental data. nOKa3aH0, YTO BO BHeZUHeM IIOJIe BbIIIIe KpElTHseCKOrO B reJIHIEOPiAaJIbHOM MarlieTElHe CSCUcl, BO3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The most interesting finding in recent years has been the evidence of phase transitions of the magnetic structure in strong external magnetic fields (Nojiri et a1 1988, Fedoseeva et al 1985, Gekht et al 1989. In the magnetization, anomalies have been seen at 1.1 K near 12 T: Noriji et al found a small vertical step in M versus H for H parallel to c, which points to a sudden flop-like change, while for H in the ab plane they found a short plateau indicating a smooth phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…The most interesting finding in recent years has been the evidence of phase transitions of the magnetic structure in strong external magnetic fields (Nojiri et a1 1988, Fedoseeva et al 1985, Gekht et al 1989. In the magnetization, anomalies have been seen at 1.1 K near 12 T: Noriji et al found a small vertical step in M versus H for H parallel to c, which points to a sudden flop-like change, while for H in the ab plane they found a short plateau indicating a smooth phase transition.…”
Section: Introductionmentioning
confidence: 99%